2019
DOI: 10.1177/0271678x19889089
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal study of cerebral blood flow regulation during exercise in pregnancy

Abstract: Cerebrovascular adaptation to pregnancy is poorly understood. We sought to assess cerebrovascular regulation in response to visual stimulation, hypercapnia and exercise across the three trimesters of pregnancy. Using transcranial Doppler (TCD) ultrasound, middle and posterior cerebral artery mean blood velocities (MCAvmean and PCAvmean) were measured continuously at rest and in response to (1) visual stimulation to assess neurovascular coupling (NVC); (2) a modified Duffin hyperoxic CO2 rebreathe test, and (3)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 37 publications
(44 reference statements)
0
5
0
Order By: Relevance
“…Regarding aim 1, 99 tests (including 75 different protocols) were used to assess CRF,8 12 13 18 27–108 28 (including 16 different protocols) to assess muscular fitness,8 12 13 61 86 109–122 14 (including 13 different protocols) to assess flexibility,12 13 110 114 123–127 45 tests (including 40 different protocols) to assess balance,110 116 128–167 2 tests using the same protocol to assess speed168 169 and 3 tests using the same protocol were multidimensional 168–170. No results were found for other PF components such as agility or coordination.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Regarding aim 1, 99 tests (including 75 different protocols) were used to assess CRF,8 12 13 18 27–108 28 (including 16 different protocols) to assess muscular fitness,8 12 13 61 86 109–122 14 (including 13 different protocols) to assess flexibility,12 13 110 114 123–127 45 tests (including 40 different protocols) to assess balance,110 116 128–167 2 tests using the same protocol to assess speed168 169 and 3 tests using the same protocol were multidimensional 168–170. No results were found for other PF components such as agility or coordination.…”
Section: Resultsmentioning
confidence: 99%
“…Of the 99 tests, a total of 75 corresponded to different protocols. For instance, there were 56 different protocols using a cycle ergometer, distributed as follows: only one article used the Arstila test68; one used the Bruce Protocol at 75% HR max 27; one applied the Modified Bruce ramp protocol at anaerobic threshold104; two employed the Modified Balke protocol at 70% HR max 34 41; one used a YMCA protocol;106 The remaining of articles (n=55) used ad hoc tests (ie, specifically designed for the purpose of the investigation); 11 of which32 37 38 41 45 57 64 79 107 used steady-state tests and 4428–31 33 35 36 39–41 43 44 46–56 59–63 65–69 90 100–106 108 171–173 used incremental tests. When analysing the type of test based on intensity, we found that 13 tests were maximal tests,31 43 44 47–49 59 60 67 103–105 171 37 submaximal tests29 30 35–40 42 45 46 50–52 54–57 62–66 68 69 79 90 100–102 106 108 172 and 3 used mixed tests28 33 41 containing submaximal and maximal stages within the same protocol.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…When CPX last longer than 12 minutes external factors, such as peripheral or psychological fatigue, can impact an individual's performance and underestimate their aerobic capacity (Balady et al, 2010a(Balady et al, , 2010b. Unless there is a clinical indication to extend exercise stages, the majority of women are able to tolerate 1-minute stages even into late pregnancy (Matenchuk et al, 2019;Purdy et al, 2018). It is also important to ensure that the CPX assessor is aware of the cardiac adaptations that occur during pregnancy (i.e., increase in resting heart rate that can impact maximal heart rate and heart rate reserve equations (Meah et al, 2016;Robson et al, 1989)) and follow pregnancy target heart rate guidelines when identifying the intensity at which an individual is working during a CPX (Mottola et al, 2018).…”
Section: Protocols and Modalitiesmentioning
confidence: 99%
“…Moreover, the gestational week could be a determinant for physiological response since Bijl et al[96] observed a slower hemodynamic recovery and an increased ventilatory response to exercise in early pregnancy compared to non-pregnant women. With regards to the maximal tests, different terms have been used like maximal criteria such as volitional fatigue[64,69,70,72,73,93,94,109,178], exhaustion[63], anaerobic threshold…”
mentioning
confidence: 99%